Sexual dymorphism in the 2nd to 4th finger formula - Drozdowski, Zbigniew (Anthropological Review, 1979)
The author has examined on a material of 1,000 males and 1,000 females frequency of 2nd==4th, 2nd longer than 4th and 2nd shorter than 4th finger patterns. Among males the most frequent pattern was “2nd shorter than 4th” (65%/o), while in females the reverse pattern prevailed (57.9%). Differences in finger patterns frequencies are statistically significant between sexes, however they are not so sharply expressed as to constitute a good diagnostic trait for ascertaining sexual dimorphism.